138k views
18 votes
Help pls, answer choices listed also

Help pls, answer choices listed also-example-1
User Lebyrt
by
6.4k points

1 Answer

8 votes

Answer:

A.

Explanation:

Hi there!

By factoring the trinomial, we end with (x-9)(x-4)

However, we aren’t done yet. To find the zeros, set each expression equal to zero, so it looks something like this.

0 = x - 9

0 = x - 4

Using orders of operations, x = 9 and x = 4

Therefore, A is your answer.

I hope this helps!

User Spandyie
by
5.8k points